Comparison of early versus delayed temporary ileostomy reversal in colorectal anastomosis - Rooh-Ul-Ain, Rizwan Ahmed Khan, Fareeha Khaliq Khan, Maaz Ul Hassan, Itrat Hussain Kazmi, Awais Bhutta, Aniqa Ejaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the outcome of early versus delayed temporary ileostomy reversal in colorectal anastomosis. Design: Randomized control clinical trials Place & period of the study: Surgical Unit 1 of the Services Hospital in Lahore from December 2017 to June 2018. Methods: A total of 176 patients, undergoing distal colorectal resections were divided randomly into group A; ileostomy reversal in less than 2 weeks after primary surgery and group B; ileostomy reversal after 8 weeks of primary surgery was followed for 4 weeks to access wound infection, abdominal pain, anastomotic leak, soreness and gut material discharge through the wound. Results: The average age of patients was 40.48+13.13years [range 18-60] in group A. In group B, the average age of patients was 41.92+14.08 [range 18 – 60]. Post-operative wound infection occurred in group A were 12 (13.63%) and in group B 8 (9.09%) while anastomotic leakage observed in 7 (8%) of group A patients and 4 (4.5%) of group B patients. Calculated p – value was 0.350 and hence not significant (p> 0.05). Conclusion: Early closing of loop de-functioning ileostomy in patients receiving distal colorectal resection is feasible and produces comparable results to delayed closure.